Systematic revision of the vizcachas (Rodentia, caviomorpha, chinchillidae) from the Chapadmalal Formation, Late Pliocene of Buenos Aires province, Argentina - Rasia, Luciano Luis (2016)
Fil: Rasia, Luciano Luis. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina